Effect of exercise on cerebral perfusion in humans at high altitude. - Imray, C; Myers, S; Pattinson, K; Bradwell, A; Chan, C; Harris, S; Collins, P; Wright, A (2005)
The effects of submaximal and maximal exercise on cerebral perfusion were assessed using a portable, recumbent cycle ergometer in nine unacclimatized subjects ascending to 5,260 m. At 150 m, mean (SD) cerebral oxygenation (rSO2%) increased during submaximal exercise from 68.4 (SD 2.1) to 70.9 (SD 3.8) (P < 0.0001) and at maximal oxygen uptake (.VO2(max)) to 69.8 (SD 3.1) (P < 0.02). In contrast, at each of the high altitudes studied, rSO2 was reduced during submaximal exercise from 66.2 (SD 2.5) to 62.6 (SD 2.1) at 3,610 m (P < 0.0001), 63.0 (SD 2.1) to 58.9 (SD 2.1) at 4,750 m (P < 0.0001), and 62.4 (SD 3.6) to 61.2 (SD 3.9) at 5,260 m (P < 0.01), and at .VO2(max) to 61.2 (SD 3.3) at 3,610 m (P < 0.0001), to 59.4 (SD 2.6) at 4,750 m (P < 0.0001), and to 58.0 (SD 3.0) at 5,260 m (P < 0.0001). Cerebrovascular resistance tended to fall during submaximal exercise (P = not significant) and rise at .VO2(max), following the changes in arterial oxygen saturation and end-tidal CO(2). Cerebral oxygen delivery was maintained during submaximal exercise at 150 m with a nonsignificant fall at .VO2(max), but at high altitude peaked at 30% of .VO2(max) and then fell progressively at higher levels of exercise. The fall in rSO2 and oxygen delivery during exercise may limit exercise at altitude and is likely to contribute to the problems of acute mountain sickness and high-altitude cerebral edema.